Prospects for Change of Bulgaria’s Population to 2040 - Borissova–Marinova, Kremena; Moraliyska–Nikolova, Stanislava (Research Papers, 2019)
The regime of demographic reproduction in Bulgaria, having been formed throughout last three decades, along with the resultant population ageing, might have some unfavourable effects on the economy’s development alternatives. The study contains a presentation of the main results of the research on Bulgaria’s demographic development prospects to 2040. For this purpose, a review of the published demographic projections for Bulgaria covering the relevant period of time and an analysis of the methodological background and the projection results were made. The analysis made covers the main demographic indices describing the possible population development over the coming 23 years: population number according the various projection variants, distributions by sex, age groups and districts. Similar trends in the demographic development of the country are outlined in all available projections of Bulgaria’s population: persistent and significant decrease of population. Although, in a European context, Bulgaria is not alone in the group of countries, whose population is projected to be decreasing and ageing, under the conditions of free of movement of persons in EU a variety of demographic indices depends more and yet more on the country’s economic growth level and rate. The analysis of projection data on the number and demographic characteristics of the population is a condition for developing realistic and well-balanced strategies for Bulgaria’s development as well as for implementing the needed policies to achieve the targets set.